TINGKAT PEMAHAMAN DAN KESIAPAN PENERAPAN ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) PADA UMKM DI SURABAYA - Putri Imeldatus Sholeha; Neza Putri Pratama; Titiek Rachmawati (Jurnal Nirta : Inovasi Multidisiplin, 2026)
This study aims to analyze the level of understanding and readiness in implementing Environmental, Social, and Governance (ESG) principles among Micro, Small, and Medium Enterprises (MSMEs) in Surabaya. The research employs a descriptive quantitative approach to depict the actual conditions in the field without examining causal relationships between variables. The data used are primary data collected through questionnaires distributed to 30 respondents selected using accidental sampling. The research instrument applies a five-point Likert scale. The variables examined include ESG understanding and ESG implementation readiness, which are measured based on environmental, social, and governance dimensions. The results indicate that the level of ESG understanding is categorized as high, with a mean score of 4.06. This suggests that MSME actors generally possess adequate knowledge regarding ESG concepts and their benefits in business activities. Meanwhile, the level of readiness for ESG implementation is also categorized as high, with a mean score of 3.96, indicating an initial capacity to adopt sustainability principles. However, a gap is identified between understanding and actual implementation, as ESG practices remain partial and have not been systematically integrated into business operations. These findings imply that increased awareness has not been fully translated into practical application. Therefore, further efforts are required, including more practical training programs, continuous assistance, and supportive policies to enhance ESG implementation among MSMEs. This study is expected to contribute to the development of ESG-related literature and serve as a reference for formulating strategies to improve ESG adoption among MSMEs in Surabaya.